(untitled) (Acta Scientiarum. Biological Sciences, 2010)
Steindachinerina brevipinna is a freshwater fish from the Curimatidae family, and its occurrence is restricted to some South American countries (Argentina, Brazil, Paraguay and Uruguay), distributed in the Paraguay, lower and upper Paraná and lower Uruguay rivers. There are no parasitological studies related to this fish. The present study records and illustrates a species of digenean, Sphincterodiplostomum musculosum from subfamily Diplostominae, present on the ovary and three species of nematodes, Cosmoxynema vianai Travassos, 1949, Travnema travnema Pereira, 1938, Spinoxyuris sp., of superfamily Oxyuridea, parasitizing the intestine of S. brevipinna collected in the tributaries Guairacá and Corvo of the Paranapanema River, Parana State, Brazil.